Analisis Kondisi Fisik Pemain Bola Voli Putra Mts Negeri 7 Jember - Rahma Roudlotul Jannah; Bahtiar Hari Hardovi2 Hari Hardovi; Ahmad Sulaiman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the physical condition of male volleyball players at MTs Negeri 7 Jember through the components of speed, agility, and endurance using a quantitative descriptive method with 12 players selected through a saturated sampling technique. Data were collected using a 30-meter sprint, the Illinois Agility Run Test, and a 1000-meter run, then analyzed using percentage classifications based on each test's assessment standards. The results showed notable variations in physical ability, with Ferbyan and Marfel achieving the highest overall condition scores at 73.4% (good category), while Ardi recorded the lowest score at 26.6% (poor category), and most players fell into the very poor category for endurance. Overall, the study concludes that the players’ physical condition remains uneven and requires a more targeted training program, particularly to improve endurance and speed. Keywords: physical condition, speed, agility, endurance, volleyball an daya tahan dan kecepatan.